The planthopper genus Epora Walker (Hemiptera: Fulgoroidea: Tropiduchidae) from China with description of one new species - Men, Qiu-Lei; Feng, Ji-Nian; Qin, Dao-Zheng (Zootaxa, 2011)
The three Chinese species of the tropiduchid genus Epora Walker are revised, including one new species, E. biprolata sp. nov. from Hainan Province, China. Morphological description or diagnoses and illustrations for Chinese Epora and an identification key for all nine species worldwide are provided.